5w+6=9-w

Add w to both sides of the equation.

5w+6+w=9

Add 5w and w.

6w+6=9

6w+6=9

Subtract 6 from both sides of the equation.

6w=9-6

Subtract 6 from 9.

6w=3

6w=3

Divide each term in 6w=3 by 6.

6w6=36

Cancel the common factor of 6.

Cancel the common factor.

6w6=36

Divide w by 1.

w=36

w=36

Cancel the common factor of 3 and 6.

Factor 3 out of 3.

w=3(1)6

Cancel the common factors.

Factor 3 out of 6.

w=3⋅13⋅2

Cancel the common factor.

w=3⋅13⋅2

Rewrite the expression.

w=12

w=12

w=12

w=12

The result can be shown in multiple forms.

Exact Form:

w=12

Decimal Form:

w=0.5

Solve for w 5w+6=9-w